2021
DOI: 10.1111/1365-2745.13662
|View full text |Cite
|
Sign up to set email alerts
|

Steering the soil microbiome by repeated litter addition

Abstract: Microbial communities drive plant litter breakdown. Litters originating from different plant species are often associated with specialised microbiomes that accelerate the breakdown of that litter, known as home‐field advantage. Yet, how and how fast microbial communities specialise towards litter inputs is not known. Here we study effects of repeated litter additions on soil microbial community structure and functioning. We set up a 9‐month, full‐factorial, reciprocal litter transplant experiment with soils an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 113 publications
2
16
0
Order By: Relevance
“…The addition of grass litter to tree soils resulted in the convergence of fungal communities to those found in grass soils incubated with grass litter and vice versa. Such steering effects are more likely driven by different chemical composition of plant litter, suggesting that microbial communities can be selected by adding particular litter, and therefore particular plant metabolite cocktails (van Dam & Bouwmeester, 2016;Veen et al, 2021). These results support our findings and highlight the urgent need in new experiments to test whether plants select particular soil microbiome.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The addition of grass litter to tree soils resulted in the convergence of fungal communities to those found in grass soils incubated with grass litter and vice versa. Such steering effects are more likely driven by different chemical composition of plant litter, suggesting that microbial communities can be selected by adding particular litter, and therefore particular plant metabolite cocktails (van Dam & Bouwmeester, 2016;Veen et al, 2021). These results support our findings and highlight the urgent need in new experiments to test whether plants select particular soil microbiome.…”
Section: Discussionsupporting
confidence: 84%
“…The exact mechanisms by which Sphagnum mosses shape their microbiome are as yet unknown, but differences in the metabolite cocktails that Sphagnum release into their surrounding are likely to be an important factor. Interestingly to mention, a recent study found that repeated litter inputs resulted in directional shifts in the composition of the soil microbiome, especially fungal communities (Veen et al, 2021). The addition of grass litter to tree soils resulted in the convergence of fungal communities to those found in grass soils incubated with grass litter and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Soil microorganisms are influenced by the input of exogenous organic matter such as litter and roots, but the magnitude of the effect is closely related to the quantity and quality of organic matter ( Fanin and Bertrand, 2016 ). Previous studies have also shown that the soil microbial community structure has different responses to the input of exogenous organic matter ( Habtewold et al, 2020 ; Veen et al, 2021 ). For example, litter addition facilitated soil fungal growth and significantly reduced the bacteria: fungi ratio in subtropical forests ( Wang et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, these limitations may cause losses in agricultural and forestry productivity, soil degradation, water deficit, reduced biodiversity, and destruction of certain valuable landscapes ( Berg et al., 2020 ; Hirsch et al., 2013 ; Stegen et al., 2018 ). Because the soil microbial community can be affected by many ecological and agronomic factors, it is reasonable to consider the effect of the environment, especially with global warming, for optimal management of the soil microbiome ( Jacoby et al., 2017 ; Veen et al., 2021 ; Zolla et al., 2013 ).…”
Section: Importance Of Microbial Community To Soil Fertility and Sustainabilitymentioning
confidence: 99%